Impact of High-intensity Intermittent and Moderate-intensity Continuous Exercise on Autonomic Modulation in Young Men - Cabral-Santos, C. [UNESP]; Giacon, T. R. [UNESP]; Campos, E. Z. [UNESP]; Gerosa-Neto, J. [UNESP]; Rodrigues, B.; Vanderlei, L. C. M. [UNESP]; Lira, F. S. [UNESP] (Georg Thieme Verlag Kg, 2016)
The aim of this study was to compare heart rate variability (HRV) recovery after two iso-volume (5km) exercises performed at different intensities. 14 subjects volunteered (25.17 +/- 5.08 years; 74.7 +/- 6.28kg; 175 +/- 0.05cm; 59.56 +/- 5.15mLkg(-1)min(-1)) and after determination of peak oxygen uptake (VO2Peak) and the speed associated with VO2Peak (sVO(2Peak)), the subjects completed 2 random experimental trials: high-intensity exercise (HIE - 1:1 at 100% sVO(2Peak)), and moderate-intensity continuous exercise (MIE - 70% sVO(2Peak)). HRV and RR intervals were monitored before, during and after the exercise sessions together with, the HRV analysis in the frequency domains (high-frequency - HF: 0.15 to 0.4Hz and low-frequency - LF: 0.04 to 0.15Hz components) and the ratio between them (LF/HF). Statistical analysis comparisons between moments and between HIE and MIE were performed using a mixed model. Both exercise sessions modified LFlog, HFlog, and LF/HF (F=16.54, F=19.32 and F=5.17, p<0.05, respectively). A group effect was also found for LFlog (F=23.91, p<0.05), and HFlog (F=57.55, p< 0.05). LF/HF returned to resting value 15min after MIE exercise and 20min after HIE exercise. This means that the heavy domain (aerobic and anaerobic threshold) induces dissimilar autonomic modification in physically active subjects. Both HIE and MIE modify HRV, and generally HIE delays parasympathetic autonomic modulation recovery after iso-volume exercise.
Keywords: high-intensity exercise; moderate-intensity continuous exercise; autonomic modulation; heart rate variability